Role of Matrix Metalloproteases and Total Antioxidant Capacity in Early Childhood Caries – A Review - Thimmegowa, Umapathy; Pai , Soumya; Nagarajshetty, Praveen Malavalli (Advanced Concepts in Medicine and Medical Research Vol. 12, 2024)
Dentistry has traditionally transitioned from the straightforward extraction of the caries-affected tooth to the treatment and restoration of the lesion in the evolution of caries therapy. A further development in dental care is the detection of early caries lesions and treatment using non-surgical techniques like remineralization. The phrases early childhood caries and rampant caries are occasionally used interchangeably. More than 25 secreted and membrane-bound enzymes collectively referred to as matrix metalloproteinases are a class of enzymes that break down pericellular substrates. The amount of free radicals scavenged by a test solution is measured as the total antioxidant capacity, which is then used to assess the antioxidant strength of biological samples. This is very important because oxidative stress can influence the beginning and development of various nflammatory and infectious disorders, including dental caries. The purpose of this review is to talk about how total antioxidant capacity and matrix metalloproteases relate to early childhood caries.